2004
DOI: 10.1111/j.1439-0396.2004.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hay intake and feeding sequence on variables in faeces and faecal water (dry matter, pH value, organic acids, ammonia, buffering capacity) of horses

Abstract: To investigate effects of hay intake and feeding sequence on indicators of the microbial activity within the hindgut, six horses were fed 1.00 kg oats plus 0.50, 0.67, 0.83 or 1.00 kg hay/100 kg body weight (BW) · day, each for 14 days. Oats was offered either 30 min prior to hay (OA) or in the reversed sequence (HA) in a 2 · 8-week crossover design. Because typically exercised horses should be subjected to the study, faeces was used as substrate. Faecal dry matter (DM), the faecal watersÕ short-chain fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
21

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 21 publications
3
35
0
21
Order By: Relevance
“…Lactate attracts water, setting the stage for osmotic diarrhea. Moreover, high-starch feeding represents a well-known risk factor for the development of gastrointestinal disorders, like lesions on the mucosal surface of the stomach and large intestine, and microecological dysfunction with colic [14]. For this reason, a diet with high content of starch should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate attracts water, setting the stage for osmotic diarrhea. Moreover, high-starch feeding represents a well-known risk factor for the development of gastrointestinal disorders, like lesions on the mucosal surface of the stomach and large intestine, and microecological dysfunction with colic [14]. For this reason, a diet with high content of starch should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the hindgut can act as a fluid reservoir when fibre-based diets are fed (Meyer, 1987), but also that fibre composition might affect water binding and reduce its availability (Cuddeford et al, 1992). This was probably the case in the present study Zeyner et al (2004). A feedstuffs ability to interact with water can be expressed as its swelling or water-binding capacity (Bach Knudsen, 2001).…”
Section: Discussionmentioning
confidence: 63%
“…The differences in the solubility and fermentability of these fibres can provide different physiological benefits and affect faecal characteristics (de-Oliveira et al 2008;Calabr o et al 2012). Several outcomes were evaluated to determine the physicochemical characteristics of faeces, such as faecal production (Kawauchi et al 2011), faecal score (Laflamme et al 2011), pH (de-Oliveira et al 2008, buffering capacity (BC) (Zeyner et al 2004) and ammonia nitrogen (Brito et al 2010).…”
Section: Introductionmentioning
confidence: 99%